Hubungan Motivasi Belajar dan Prestasi Akademik Mahasiswa Prodi Akuntansi Fakultas Ekonomi dan Bisnis Universitas 17 Agustus 1945 Surabaya - Yulita Alfonsia Hayon; Hwihanus Hwihanus (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the factors that influence the academic achievement and motivation of students in the Accounting Study Program, Faculty of Economics and Business, University of 17 August 1945 Surabaya. Achievement is one of the important academic indicators in reflecting the success of the learning process in higher education. The research results show that student learning motivation has a significant influence on academic achievement, followed by effective teaching methods and the availability of supporting facilities. Social environmental support, such as the role of family and peers, was also found to have a positive contribution. . These findings have the impact that improving the quality of learning and providing holistic support can help students achieve persistence,